Major Topics in Type 1 Diabetes - Pedrosa Nunes, Kenia (IntechOpen, 2015)
Type 1 diabetes (TD1) is one of the most common endocrine disorders in children and can occur at any age. Incidences of T1D have steadily increased worldwide, and it is largely considered an autoimmune disorder resulting from the specific destruction of pancreatic beta-cells producing insulin. However, T1D pathophysiology is still not completely understood, and although insulin and other therapies ameliorate the manifestations of the disease, no cure is currently available. This book has been written by widely acknowledged experts, with each chapter providing unique information on emerging aspects of T1D. Because a large body of information has been available regarding T1D, this book highlights lesser explored topics linked to the subject using important and recent knowledge that presages directions for further research. Current possibilities to forestall diabetic complications are also explored.